Menggali Filsafat Wayang Beber untuk Mendukung Perkembangan Industri Kreatif Batik Pacitan - Suyanto, Suyanto (PANGGUNG, 2017)
AbstractThis article entitled "Digging the Wayang Beber Philosophy to Encourage the Development of Creative Industries of Batik in Pacitan Regencyâ. It is the juice from the results of our research in the second year. This research was conducted to look at the extent to which the condition of the Wayang Beber Pacitan its relationship with growth and development of industrial and economic aspects, as well as her role as media strengthening local wisdom and efforts increase the economy of communities in Pacitan Regency.This research uses the theory of action research approach through four stages; first determine the focus of the second, the third data collection, analysis and interpretation of data, and a fourth action field. The method is carried out in several stages: the stage of the Assessment, the design stages, the stages of socialization, mentoring and training stages, the stages of production, and the stages of launching. Results of the study in the second year it has also become the third year research reference i.e. dissemination draft corporate identity branding guide ecotourism village of batik and a draft training module design motifs reserved for industrial cluster batik craftsmen so able to improve the economy of Pacitan Regency society.Keywords: Philosophy of Wayang Beber, Batik Motif Pacitan, and Improving the Economy of the Community.Abstrak Artikel ini berjudul âMenggali Filsafat Wayang Beber Untuk Mendorong Perkembangan Industri Kreatif Batik di Kabupaten Pacitanâ Ini merupakan perasan dari hasil penelitian kami pada tahun kedua. Penelitian ini dilakukan untuk melihat sejauh mana kondisi Wayang Beber Pacitan hubungannya dengan pertumbuhan dan perkembangan aspek ekonomi dan industri, serta perannya sebagai media penguatan kearifan lokal dan upaya peningkatan perekonomian masyarakat di Kabupaten Pacitan. Penelitian ini menggunakan pendekatan teori action research melalui empat tahapan; pertama menentukan fokus, kedua pengumpulan data, ketiga analisis dan interpretasi data, dan keempat tindakan lapangan. Metode yang dilakukan dalam beberapa tahapan : Tahapan Pengkajian, Tahapan Perancangan, Tahapan Sosialisasi, Tahapan Pendampingan dan Pelatihan, Tahapan Produksi, dan Tahapan Launching. Hasil penelitian pada tahun kedua ini juga menjadi acuan penelitian tahun ketiga yaitu desiminasi draft corporate identity branding panduan ekowisata kampung batik dan draft modul pelatihan perancangan desain motif batik yang diperuntukkan bagi pengrajin klaster industri batik Pacitan sehingga mampu meningkatkan perekonomian masyarakat Kabupaten Pacitan.Kata Kunci: Filsafat Wayang Beber, Motif Batik Pacitan, dan Peningkatan Perekonomian Masyarakat